Multicomponent combinatorial synthesis of proplyl peptide-lipopeptoid hybrid catalyst: application in the asymmetric Michael addition under aqueous environment - Delgado, José Antonio Campos (Universidade Federal de São Carlos, 2018)
This study describes the synthesis of a new library of prolyl peptides-lipopeptoid hybrids catalysts through a multicomponent combinatorial approach. For the design of this catalyst library, we took into consideration the growing interest in the development of environmentally friendly technologies and the recent contributions of our research group in their field. To this end, by using the Ugi-four component protocol we have incorporated lipidic side chains in the architecture of the proyl peptide-peptoid hybrid catalyst. The insertion of functionalities with amphiphilic properties afford to the organocatalyst surfactant properties. Therefore, they have been further evaluated as an organocatalysts in the environmentally friendly enantioselective addition of aldehydes to nitrostyrenes. The Michael adducts were obtained in high yields, diastereoselectivities and excellent enantioselectivities using low catalyst loading under water as solvent without addition of any other additive.
Síntese combinatoria multicomponente de catalisadores prolil peptídeo-lipopeptóides híbridos: aplicação na adição de Michael assimétrica em meio aquoso
Keywords: Organocatalisadores de lipopeptídeos N-alquilados; Reações multicomponentes à base de isocianeto; Adições de Michael assimétricas; Ambiente aquoso; N-alkylated lipopeptide organocatalysts; Isocyanide-based multicomponent reactions; Asymmetric Michael additions; Aqueous environment; CIENCIAS EXATAS E DA TERRA::QUIMICA